Pengaruh Financial Distress, Leverage Dan Ukuran Perusahaan Terhadap Tax Avoidance Pada Perusahaan Food And Beverages Yang Terdaftar Di BEI Tahun 2015 - 2020 - Variska Juanda (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The target of this study is to evaluate the simultaneous and partial influence of Financial Distress, Leverage, and Firm Size to Tax Avoidance. The data of the research contains of quantitative research using secondary data of annual company financial statements. The population of this research is focused on food and beverages company listed in Indonesia Stock Exchange from 2015- 2020. The population of food and beverages companies are 30 in total, 14 of them are qualified. 63 data from 14 companies are taken as the samples of the research. This research involves multiple linear regression analysis to analyze the simultaneous and partial influence of each variable. The result of this research shows that financial distress and leverage variable have significant influence to tax avoidance partially. Whilst firm size has no influence to tax avoidance. On the other hand, financial distress, leverage and firm size have a significant influence to tax avoidance. Keywords : Financial Distress, Leverage, Firm Size, Tax Avoidance